Efficacy of the bleeding risk scoring system for optimal prophylactic anticoagulation therapy of venous thromboembolism in trauma patients: a single-center, retrospective, observational cohort study - Atsushi Tomizawa; Takaaki Maruhashi; Akito Shibuya; Akihiko Akamine; Masayuki Kuroiwa; Yuichi Kataoka; Yasushi Asari; Koichiro Atsuda; Katsuya Otori (Journal of Pharmaceutical Health Care and Sciences, 2023)
Abstract Background We developed a bleeding risk scoring system (BRSS) using prophylactic anticoagulation therapy to comprehensively assess the risk of venous thromboembolism (VTE) in trauma patients. This study evaluated the usefulness of this system in trauma patients, with a focus on minimizing the rate of bleeding events associated with prophylactic anticoagulation therapy. Methods We retrospectively evaluated the efficacy of BRSS in trauma patients who received prophylactic anticoagulation therapy for VTE at the Kitasato University Hospital Emergency and Critical Care Center between April 1, 2015, and August 31, 2020. To compare the incidence of bleeding events, patients were divided into two groups: one group using the BRSS (BRSS group) and another group not using the BRSS (non-BRSS group). Results A total of 94 patients were enrolled in this study, with 70 and 24 patients assigned to the non-BRSS and BRSS groups, respectively. The major bleeding event rates were not significantly different between the two groups (BRSS group, 4.2%; non-BRSS group, 5.7%; p = 1.000). However, minor bleeding events were significantly reduced in the BRSS group (4.2% vs.27.1%; p = 0.020). Multivariate logistic regression analysis showed that BRSS was not an independent influencing factor of major bleeding events (odds ratio, 0.660; 95% confidence interval: 0.067-6.47; p = 0.721). Multivariate logistic regression analysis showed that BRSS was an independent influencing factor of minor bleeding events (odds ratio, 0.119; 95% confidence interval: 0.015-0.97; p = 0.047). The incidence of VTE did not differ significantly between groups (BRSS group, 4.2%; non-BRSS group, 8.6%; p = 0.674). Conclusions BRSS may be a useful tool for reducing the incidence of minor bleeding events during the initial prophylactic anticoagulation therapy in trauma patients. There are several limitations of this study that need to be addressed in future research.